Proteomic Analysis of Generative and Vegetative Nuclei Reveals Molecular Characteristics of Pollen Cell Differentiation in Lily - You, Chen; Zhang, YuPing; Yang, ShaoYu; Wang, Xu; Yao, Wen; Jin, WeiHuan; Wang, Wei; Hu, XiuLi; Yang, Hao (Frontiers in Plant Science, 2021)
In plants, the cell fates of a vegetative cell (VC) and generative cell (GC) are determined after the asymmetric division of the haploid microspore. The VC exits the cell cycle and grows a pollen tube, while the GC undergoes further mitosis to produce two sperm cells for double fertilization. However, our understanding of the mechanisms underlying their fate differentiation remains limited. One major advantage of the nuclear proteome analysis is that it is the only method currently able to uncover the systemic differences between VC and GC due to GC being engulfed within the cytoplasm of VC, limiting the use of transcriptome. Here, we obtained pure preparations of the vegetative cell nuclei (VNs) and generative cell nuclei (GNs) from germinating Lily pollens. Utilizing these high purity VNs and GNs, we compared the differential nucleoproteins between them using state-of-the-art quantitative proteomic techniques. We identified 720 different amount proteins (DAPs) and grouped the results in 11 fate differentiation categories. Among them, we identified 29 transcription factors (TFs) and 10 cell fate determinants. Significant differences were found in the molecular activities of vegetative and reproductive nuclei. The TFs in VN mainly participate in pollen tube development. In comparison, the TFs in GN are mainly involved in cell differentiation and male gametogenesis. The identified novel TFs may play an important role in cell fate differentiation. Our data indicate also differences in nuclear pore complexes and epigenetic modifications: more nucleoporins synthesized in VN; more histone variants and chaperones; structural maintenance of chromosomes (SMCs) proteins, chromatin remodelers, and DNA methylation related proteins expressed in GN. The VC has active macromolecular metabolism and mRNA processing, while GC has active nucleic acid metabolism and translation. Moreover, the members of unfolded protein response (UPR) and programmed cell death accumulate in VN, and DNA damage repair is active in GN. Differences in the stress response of DAPs in VN vs. GN were also found. This study provides a further understanding of pollen cell differentiation mechanisms, and also a sound basis for future studies of the molecular mechanisms behind cell fate differentiation.